Actinomycosis of the larynx - İNANLI, SELÇUK (TAYLOR & FRANCIS LTD, 2007)
Actinomycosis is a rare chronic granulomatous disease that involves the upper airway and gastrointestinal tract. Approximately 40-55% of actinomycosis comprises the cervicofacial form. It presents a challenging clinical diagnostic dilemma because of variable presentations in the head and neck. Herein, we report a rare case of actinomycosis presenting as a vocal cord nodule in a healthy 21-year-old man who was not immunocompromised and had no other known medical disease.
Keywords: actinomycosis; vocal nodule; COMPLICATION